2021
DOI: 10.3390/ani11030874
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of a New Bite Force Measure and Biomechanics of Modified Long Attack in Police Dogs

Abstract: Information on the biomechanics of police dogs’ tasks is important in understanding their work-related injuries and dysfunctions. This study aimed to develop and test a measurement tool for dogs’ functional bite force and to report modified long attack-related kinetic and kinematic values. Twenty Finnish male police dogs, 7 German Shepherd Dogs (GSDs) and 13 Belgian Shepherd Dogs, Malinois (BSDMs), were included. Dogs accelerated 25 m and bit the helper’s sleeve, fitted with three force sensors. Dogs were wear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
(27 reference statements)
1
4
0
Order By: Relevance
“…Despite the evidence of the high physical demands dogs are subjected to during bite tasks in protection work [8], the results in our study indicate that neck injuries are uncommonly reported and the injury proportion is remarkably low compared to North American samples of agility dogs [32]. The proportions between countries and geographic regions already differed, according to a previous study, which supports our findings [32].…”
Section: Anatomical Injury Locationssupporting
confidence: 71%
See 1 more Smart Citation
“…Despite the evidence of the high physical demands dogs are subjected to during bite tasks in protection work [8], the results in our study indicate that neck injuries are uncommonly reported and the injury proportion is remarkably low compared to North American samples of agility dogs [32]. The proportions between countries and geographic regions already differed, according to a previous study, which supports our findings [32].…”
Section: Anatomical Injury Locationssupporting
confidence: 71%
“…The dogs' success depends on their ability to jump, retrieve objects, perform scent tasks, focus on precision movement during heelwork, i.e., the dog's shoulder remaining level with the handler's leg throughout various maneuvers, and to complete tasks without faults according to a judge and dog sport-specific regulations [6,7]. The physical and mental requirements vary among disciplines, where disciplines such as agility, obedience, and utility involve tasks that require muscle strength and power, while rally obedience has a lower physical impact [1,7,8]. Utility disciplines, like tracking, searching and messenger, demand cardiorespiratory and muscular endurance from the dog [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…However, there were exceptions for some of the countries: two out of three of the included studies from Austria ( 54 , 55 ) were from the same group applying the same methods, and the two studies from Denmark used AMG ( 56 , 57 ). Further, five out of six studies from Finland were from the same research group but applied different methods in the studies ( 6 , 27 , 35 , 47 , 58 ). Accordingly, the included 12 studies from Germany were conducted by four research groups ( 59 70 ).…”
Section: Resultsmentioning
confidence: 99%
“…Tools for measuring bite force continue to be developed, however, we can provide an approximation of expected bite forces per breed and by weight. Hyytiäinen et al constructed a bite sleeve embedded with compression force sensors and found that on average German Shepherd Dogs (GSD) (n = 7) and Belgian Shepherd Dogs, Malinois (BSDMs) (n = 13) police dogs produced a median bite force of 360.4 Newton (N) and 247.0 N, respectively (45). Lindner et al ( 46) use a rawhide-covered force transducer to measure bite force across 22 pet dogs that range in weight and size.…”
Section: Bite Force Estimationsmentioning
confidence: 99%